Research on Monetary Policy Implementation and Industrial Structure Transformation Under COVID-19—Evidence From Eight Economic Zones in Mainland China - Zhou, Baicheng; Wang, Shu; Gao, Henan; Wang, Han (Frontiers in Public Health, 2022)
The outbreak of COVID-19 has brought a serious impact on the economies of various countries, monetary policy needs to play a role in stimulating economic recovery when the economy encounters a serious negative impact. Since the recurrent outbreak of COVID-19 has caused great obstacles to the normal economic exchanges between countries, it has become particularly important to build the domestic market and optimize the industrial allocation at this time. This paper focuses on studying the dynamic impact of China's monetary policy implementation on the industrial structure during the pandemic. Based on the data of the eight major economic zones in Mainland China and the dataset containing many of China's macroeconomic variables, a SV-TVP-FAVAR model is established. The manuscript compares the time-varying effects of monetary policy tools on the industries at different stages before and after the epidemic. The study supported some interesting conclusions. (1) Either the quantitative or price-based monetary policy shocks have significant time-varying impacts on the industries in different economic zones. The impacts of monetary policy on the primary, secondary, and tertiary industries in each economic zone are uneven. (2) The developed Northern, Eastern, and Southern coastal economic zones in Mainland China are more sensitive to the changes in monetary policy. (3) COVID-19 has brought a tremendous negative shock on the economy, which has destroyed the original steady-state of the economic system and added more uncertainty to the regulatory effect of monetary policy. Compared with other periods in China's economic history that severely negatively impacted (the Southeast Asian financial crisis and the global economic crisis), industries in most economic zones under the COVID-19 epidemic have been affected by monetary policy for a longer lag time. Therefore, for the implementation of monetary policy, at the moment of COVID-19 epidemic, we should pay more attention to the dual-pillar role of macro-prudential regulation, further improve the process of China's interest rate reform, enrich the monetary toolbox, and implement differentiated monetary policies in line with the economic zone's position, to optimize the regional industrial structure, and promote long-term economic growth.